Relações entre pintura, fotografia e imagem na arte contemporânea - Lemos, Andreia Falqueto (2017)
Beginning the reflection with modernism in art and the advent of photography, this research intends to make a study of the relations of photography and painting through the history of modern art, choosing works of art and art’s theories to base these refl